2021
DOI: 10.1021/acs.oprd.1c00033
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Practical, Two-Step Process for Molnupiravir: Direct Hydroxamination of Cytidine Followed by Selective Esterification

Abstract: A two-step synthesis of molnupiravir (1) is presented. This work focuses on the development of practical reaction and purification conditions toward a manufacturing route. The sequence commences from highly available cytidine (2), and molnupiravir is formed through direct hydroxamination of the cytosine ring and esterification of the sugar’s primary alcohol without use of protecting or activating groups. A highly crystalline hydrate of N-hydroxycytidine (3) resulted in an easily purified intermediate, and a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(64 citation statements)
references
References 12 publications
2
62
0
Order By: Relevance
“…Furthermore, while the signals for the H1 hydroxyl protons are shown almost in the same region at 2.33-2.90 ppm, the signals for the other hydroxyl protons, together with the signals for the NH protons, vary from 2.87 to 7.88 ppm (Table 7). Notably, the calculated 1 H NMR spectra of both the keto-oxime and hydroxyl-oxime tautomers agree with the experimental one [26]. Since the experimental spectrum was recorded in methanol-d 4 , thus, vanishing plausible signals from the hydroxyl and amine hydrogens, it is impossible to clearly attribute the exact tautomer of the mentioned two.…”
Section: Resultssupporting
confidence: 70%
“…Furthermore, while the signals for the H1 hydroxyl protons are shown almost in the same region at 2.33-2.90 ppm, the signals for the other hydroxyl protons, together with the signals for the NH protons, vary from 2.87 to 7.88 ppm (Table 7). Notably, the calculated 1 H NMR spectra of both the keto-oxime and hydroxyl-oxime tautomers agree with the experimental one [26]. Since the experimental spectrum was recorded in methanol-d 4 , thus, vanishing plausible signals from the hydroxyl and amine hydrogens, it is impossible to clearly attribute the exact tautomer of the mentioned two.…”
Section: Resultssupporting
confidence: 70%
“…Uridine is a costly starting material. Therefore, some new patented/non patented routes for the synthesis of molnupiravir utilizing cheaper starting materials (cytidine) have also been developed [31][32][33]60,61]. Our patent search also revealed IN202121014827A [62], IN202121005152A [63], and IN202141011933A [64], which also cover processes for preparing molnupiravir.…”
Section: Expert Opinionmentioning
confidence: 99%
“…This four-step route used low-cost reagents to produce molnupiravir in an overall 44% yield 10 . Recent inquiry has shown that cytidine is available on the commercial marketplace in the multi-metric ton scale 11 .…”
Section: Introductionmentioning
confidence: 99%